Limitation of Non-Halal Income (Interest) in The Criteria of Sharia Securities List in Indonesia Stock Exchange - M Fatchurrohman; Pungky Lela Saputri (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2022)
The Islamic capital markets in Indonesia have been developing over the last two decades, characterized by an increase in Islamic products and the issuance of regulations related to the Islamic capital markets, and the general public and investors are beginning to understand the list of Islamic securities. Next, there is  one of the controversial criteria for the Sharia Securities List. That is, the total yield is less than 10%. It is understandable whether Islamic financial institutions earn income from bank interest before they are fully subject to Sharia law. Puprose: The purpose of this research is to examine the refinement of several regulations related to criteria and issuance of sharia lists to encourage and increase the Indonesian Sharia Stock Index (ISSI). Methodology: This study analyzes the dispute using an associative  approach by building relationships between social situations or domains based on the interdependencies of the dispute under study. It is a study to do. Result: The results of this survey and discussion are based on an analysis of non-Halal income (interest) restrictions in the criteria for listing Shariah securities in Indonesia to address the conditions, risks and possibilities of Sharia Securities List (SSL). The Indonesian capital markets industry is beginning to develop the application of the Islamic Shariah Principles as an alternative investment tool in Indonesian capital market activities. With the standard requirements and the issuance of the following list of Shariah securities, total interest income and other non-Halal income for each security will be less than 10%. The decision to change the issuer's financial indicators was analyzed by capital market authorities on the effect that the company continues to use interest-based financial institutions. If the interest limit is kept to a minimum, the capital market will not run and develop properly and will inevitably lead to a drastic decline in the Islamic stock index on IDX. Thus, when Islamic issuers have developed a lot and are finally ready to lower the interest-based non-halal income limit, they will certainly have a perspective in influencing the conditions of inclusion of other Islamic financial institutions.